Pediatric Melanoma and Drug Development - Klaus Rose; Jane M. Grant-Kels (MDPI AG, 2018)
Importance-Pediatric melanoma occurs, albeit rarely. Should patients be treated by today's medical standards, or be subjected to medically unnecessary clinical studies? Observations-We identified international, industry-sponsored pediatric melanoma studies triggered by regulatory demands in www.clinicaltrials.gov and further pediatric melanoma studies demanded by European Union pediatric investigation plans. We retrieved related regulatory documents from the internet. We analyzed these studies for rationale and medical beneficence on the basis of physiology, pediatric clinical pharmacology and rationale. Regulatory authorities define children by chronological age, not physiologically. Newborns' organs are immature but they develop and mature rapidly. Separate proof of efficacy in underage patients is justified formally/regulatorily but lacks medical sense. Children-especially post-puberty-and adults vis-a-vis medications are physiologically very similar. Two adolescent melanoma studies were terminated in 2016 because of waning recruitment, while five studies in pediatric melanoma and other solid tumors, triggered by European Union pediatric investigation plans, continue recruiting worldwide. Conclusions and Relevance-Regulatory-demanded pediatric melanoma studies are medically superfluous. Melanoma patients of all ages should be treated with effective combination treatment. Babies need special attention. Children need dose-finding and pharmacokinetic studies but adolescents metabolize and respond to drugs similarly to adults. Institutional Review Boards/ethics committees should suspend ongoing questionable pediatric melanoma studies and reject newly submitted questionable studies.